Ứng dụng “mô hình lớp học đảo ngược” trong đào tạo sinh viên sư phạm: Lợi ích, thách thức và gợi ý cho Việt Nam - Tiêu, Thị Mỹ Hồng (Tạp chí Giáo dục, 2026)
In the context of digital transformation, teacher education institutions face growing pressure to innovate pedagogical practices and equip future teachers with 21st-century competencies. This study presents a scoping review synthesizing international and Vietnamese evidence on the use of the flipped classroom (FC) in pre-service teacher education. The review was guided by three objectives: (1) to synthesize reported benefits of FC, (2) to examine key challenges in its implementation, and (3) to propose context-appropriate recommendations for Vietnam. From 76 retrieved documents, 24 documents meeting the criteria were selected for aggregation and analysis. Findings highlight four benefits: fostering personalized learning and self-regulation, enhancing motivation and collaboration, linking theory with practice, and strengthening digital competencies. At the same time, four categories of barriers were identified: limited readiness and digital skills of teacher educators, insufficient self-regulation and time management among students, technological and class-size constraints, and lack of institutional or systemic support. Recommendations include professional development through the TPACK framework, early training in self-regulated learning, investment in digital infrastructure and resources. The study notes limitations, including the predominance of small-scale qualitative studies and the scarcity of empirical evidence from Vietnam. Future research should conduct large-scale studies to evaluate the long-term impact of FC on teacher preparation.